PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN DALAM MELAKUKAN PEMBELIAN PADA UD. MITRA MUDA DI KABUPATEN JEMBER - Hayatul Maspufah (STIE Mandala Jember, 2018)
The title in this research is The Influence of Marketing Mix On Consumer Decision UD. Mitra Muda in Jember. This research explains about the influence of product variables, price, place, promotion has a role in decision making in making purchases at UD. Mitra Muda. Tests conducted on four independent variables and one dependent variable, the method of analysis used is the method of Multiple Linear Regression. Based on the results of the research, it can be concluded that the Marketing Mix Variables (Product, Price, Place, and Promotion) simultaneously or together have a positive and significant influence on Consumer Purchase Decision at UD. Mitra Muda with F count> F table equal to 48,936> 2,47 with significance level of 0,000 <0,05, and variable which is very dominant is price variable with t value> t table equal to 9,387> 1,985.Keywords : marketing mix, product, price, place, promotion, consumer decision making.